Esophagitis dissecans superficialis: subdiagnosed entity in multi-morbid patients - Berrospi Castillo, Diego (2023)
A 76-year-old patient presents multiple comorbidities and gastrointestinal symptoms. The upper gastrointestinal endoscopy exam reveals distal stiffness esophageal mucosa. A biopsy was taking creating sloughing of 20 mm long by 6 mm wide with self-limited bleeding. Specimen is compatible with Esophagitis Dissecans Superficialis (EDS). This is a rare entity first described in 1800, characterized endoscopically by mucosal detachment in vertical strips like “gift paper tape”, which is confirmed by pathology with a mucosa with “two tones”, composed of a eosinophilic superficial layer and a normal-appearing basophilic area. It may be accompanied by minimal focal inflammation. The etiopathogenesis is not clear; however, it has a good response to proton pump inhibitors (PPIs). In our case, the patient presented all the characteristics of EDS, and given its low reported frequency, a review of the literature and discussion of this rare entity was performed.